Automated alignment in mask‐free photolithography enabled by micro‐LED arrays. Issue 19 (31st May 2021) - Stonehouse, M.; Blanchard, A.; Guilhabert, B.; Zhang, Y.; Gu, E.; Watson, I. M.; Herrnsdorf, J.; Dawson, M. D.
Abstract: We present an automated control system for micro scale positioning, based on single pixel imaging and fluorescence. By projecting a chequerboard array of CMOS controllable μ‐LEDs at a suitable wavelength, we are able to spatially locate, track and automatically align to fluorescent markers. Positioning is demonstrated with accuracy on the order of 20 μm. We present a maskless photo‐lithography system using the automated control capability and a second μ‐LED array to photo‐cure customisable structures in photoresist with alignment referenced to the fluorescent markers.